Risk assessment of distribution coefficient from 137Cs measurements - Kulahci, Fatih; Sen, Zekai (Springer, 2009)
Classically distribution coefficient is defined as the ratio of solid total element concentration to surface water total concentration. This coefficient is obtained from the ion measurements in the Keban Dam, Turkey, which supplies water for domestic, irrigation and hydroelectric energy generation purposes. The measurements of Cs-137 are carried out in 40 different sites and the general risk formulation and application is achieved for the distribution coefficient. The models are of exponential type and the spatial independence of the data is considered. Various charts are prepared for a set of risk levels as 5%, 10%, 20%, 25%, and 50%.
Keywords: Probability distribution function; Radionuclide; Risk assessment; Stochastic model; Water